Ikonografia śmierci w polskim malarstwie fantazji i baśni w wieku XIX - Jedlińska, Eleonora (Acta Universitatis Lodziensis. Folia Historica, 2002)
The trend of fantasy art originating from the interest of the ethnographical and historical researches as well as from the studies of religious and archaeology came into existence in Poland in the 1840s and 1850s. There were few Polish artists who dealt with the fantasy art; Ignacy Gierdzicjewski, Artur Grottger and Witold Pruszkowski are among the most important ones. The works of the fantasy trend discussed problems of the life and the death, the here after life, demons, fairy-tales, and folktales. In the fantasy paintings some typical for the romantic iconography cemetery motives such as skulls, crossbones, sepulchral crosses and ruins of castles are present. Gierdzicjewski was painting gloomy, demonical, hallucinatory visions of the Mazovian’s plains, haunted by the suffering souls. Pruszkowski’s fantasy paintings were full of realism, firmly connected with the reality, in such a manner that the nightmarish scenes seemed to be eternally included into human’s existence. Grottger was linking up fantasy events and the ones connected with the fights for national independence, wars, and misery of life in the subjugated motherland. The fantasy art used iconographic motives coming from far religious traditions, pagan, popular beliefs, fairy-tales and myths.